Systematic analysis of the prognosis and immune infiltration of E2Fs in thyroid carcinoma - Fu, Xinghao; Zhou, Xing; Ji, Feihong; He, Qi; Qiu, Xinguang (Frontiers in Genetics, 2023)
Purpose: To evaluate the diagnostic and prognostic utility of E2F transcription factors (E2Fs) in thyroid carcinoma (THCA) and its association with immune infiltration. Methods: The transcription and protein levels of E2Fs in THCA tissues were examined using the R language and the Human Protein Atlas (HPA) database in this research. We utilized UALCAN database and GEPIA2 database to analyze the association among the level of E2Fs and the clinicopathological features of thyroid carcinoma. To study the prognostic utility of E2Fs expression in THCA by R language and gene set cancer analysis (GSCA) database. Overrepresentation analysis (ORA) and gene set enrichment analysis (GSEA) were devoted to analyze the effect of E2Fs family members. TISIDB database and tumor immune estimation resource (TIMER) database were devoted to investigate the relationship among E2Fs expression and the level of immune infiltration of thyroid cancer.Results: The E2Fs are highly conserved in thyroid carcinoma and rarely mutated. E2Fs are strongly expressed in THCA and is highly related with the clinicopathological stage of thyroid carcinoma. Patients with thyroid carcinoma have a poor prognosis when E2Fs are highly expressed. The function of E2Fs in thyroid carcinoma may be closely related to renin-angiotensin system (Ras) signaling pathway, platelet derived growth factor (PDGF) signaling pathway, apoptosis and immune response. With regard to the immune infiltration, E2Fs expression and tumor infiltrating lymphocytes exhibited a positive connection.The level of E2Fs is connected with the prognosis and immune infiltration level of thyroid carcinoma, revealing that E2Fs may be a prognostic and immune infiltration cell marker in THCA patients.